BS ISO 23946. Fine ceramics (advanced ceramics, advanced technical ceramics). Test methods for optical properties of ceramic phosphors for white light emitting diodes using a Gonio-spectrofluorometer. (2nd June 2020) - British Standards Institution,
No abstract available